PERAN KELUARGA DALAM MENDIDIK ANAK - silvia angga eni (Smart Kids: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
This paper aims to describe how the role of the family in educating children. The family, who brings a child into this world, by the nature of the task of educating the child. The entire contents of the family's early personal charge of the child. Parents with an unplanned basis inculcate the habits inherited from ancestors and other influences that it receives from the community. The family is the first social group with whom the child is identified, children spend more time with family than a group with other social groups. Family members are the most significant people in a child's life, so the role of each member of the family to the education of children is necessary so that the child can become a person of value, ethics and morals for himself or for others in the vicinity.This paper aims to describe how the role of the family in educating children. The family, who brings a child into this world, by the nature of the task of educating the child. The entire contents of the family's early personal charge of the child. Parents with an unplanned basis inculcate the habits inherited from ancestors and other influences that it receives from the community. The family is the first social group with whom the child is identified, children spend more time with family than a group with other social groups. Family members are the most significant people in a child's life, so the role of each member of the family to the education of children is necessary so that the child can become a person of value, ethics and morals for himself or for others in the vicinity.